Influence of Different Nitrogen Sources on Growth and Pathogenic Capability of Rhizoctonia solani Causing Root Rot of Faba Bean - Maha Mohamed (Arab Universities Journal of Agricultural Sciences, 2019)
ABSTRACT The effect of different nitrogen sources (glucosamine sulfate, ammonium sulfate, aspartic acid, phenylalanine and peptone) in comparison to sodium nitrate, the major nitrogen compound in basal agar Czapek’s synthetic medium growth were studied on the linear growth of Rhizoctonia solani and its pathogenicity on faba bean germinated seeds. Ammonium sulfate exhibited faster liner growth and showed the same effect as the basal medium with sodium nitrate while, glucosamine sulfate showed less growth rate compared with sodium nitrate. Glucosamine sulfate and ammonium sulfate showed significant reduction in number of infection cushions which led to significant decrease of disease index in vitro. Our results showed strongly significant positive correlations between disease index and both of diameters of hyphae and number of infection cushions while, very weak correlation coefficient was found between disease index and linear growth of R. solani. Under greenhouse conditions, glucosamine sulfate or peptone as a sole nitrogen sources in food requirements of Rhizoctonia solani inoculum depressed the virulence of the fungus. The effect of different amounts of glucosamine sulfate was determined on fungal growth rate, infection cushions, disease index in vitro and polyphenol oxidase activity. Increasing amount of glucosamine sulfate showed significantly reduction of growth rate in comparison to the basal medium with sodium nitrate. All seeds subjected to R. solani grown on different amount of glucosamine sulfate showed the lower number of infection cushions, disease index and polyphenol oxidase activity compared with sodium nitrate. Under greenhouse conditions, disease index showed significantly decreased effect when glucosamine sulfate used as soil applications and showed better effect on shoot weight and root weight compared with control plants treated with sodium nitrate. Our study proposes that glucosamine sulfate may acts as controlling factor of pathogenicity genes of R. solani. Key words: Rhizoctonia solani, faba bean, Vicia faba, nitrogen sources, glucosamine sulfate, pathogenicity.